Ecological Sustainability as a Conservation Concept - J. Baird Callicott; Karen Mumford (Conservation Biology, 1997)
Neither the classic resource management concept of maximum sustainable yield nor the concept of sustainable development are useful to contemporary, nonanthropocentric, ecologically informed conservation biology. As an alternative, we advance an ecological definition of sustainability that is in better accord with biological conservation: meeting human needs without compromising the health of ecosystems. In addition to familiar benefit‐cost constraints on human economic activity, we urge adding ecologic constraints. Projects are not choice‐worthy if they compromise the health of the ecosystems in which human economic systems are embedded. Sustainability, so defined, is proffered as an approach to conservation that would complement wildlands preservation for ecological integrity, not substitute for wildlands preservation.